2000
DOI: 10.1002/1520-6777(2001)20:1<53::aid-nau7>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early pelvic floor rehabilitation after transurethral resection of the prostate

Abstract: We examined the results of teaching pelvic floor muscle exercises (PME) on micturition parameters, urinary incontinence, post-micturition dribbling, and quality of life in patients after transurethral prostatectomy (TURP). Fifty-eight consecutive patients who were selected to undergo TURP for benign prostatic hyperplasia (BPH) were admitted into the study: 28 were randomly assigned to a control group (A), 30 formed the investigational group (B) during an initial visit conducted before surgery. In group B patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1
8

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 13 publications
1
46
1
8
Order By: Relevance
“…Previous studies showed that early pelvic floor rehabilitation after transurethral prostatectomy provides significantly better satisfaction with life [35,36]. In our study, the presence of urge incontinence postoperatively did not correlate with the QoL index in either group of our patients.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Previous studies showed that early pelvic floor rehabilitation after transurethral prostatectomy provides significantly better satisfaction with life [35,36]. In our study, the presence of urge incontinence postoperatively did not correlate with the QoL index in either group of our patients.…”
Section: Discussioncontrasting
confidence: 64%
“…Pelvic floor muscle exercise is usually recommended for early postoperative micturition problems with satisfactory results [35,36]. The effectiveness of tolterodine in treating OAB symptoms as well as its tolerability have been established by a series of clinical studies [37][38][39][40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have evaluated the efficacy of treatment measure including early pelvic floor muscle exercise (PFME) or anticholinergic medications to alleviate storage symptoms such as UUI and, thereby, improve QOL in the early postoperative period after TURP [12,[14][15][16]. The previous studies showed that early PFME, which was started immediately after removal of urethral catheter, reduced UUI in the first few weeks after TURP [12,14].…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies showed that early PFME, which was started immediately after removal of urethral catheter, reduced UUI in the first few weeks after TURP [12,14]. Hou et al [15] reported that the group with immediate initiation of PFME had greater improvement in subtotal storage symptom score and QOL than control group at 12 weeks after TURP.…”
Section: Discussionmentioning
confidence: 99%
“…Un certain nombre d'études en ont étudié les indications et les résultats, certaines d'entre elles étant scientifiques, randomisées et avec groupe témoin, et d'autres relatant davantage une expérience et une étude de population [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionunclassified